Theoretical data and graphical methodological recommendations on the teaching of fortifications topics - Kurbanazarova Ugiloy Bekpulatovna; Turayev Khumoyiddin Abdugafforovich (Research Parks Publishing LLC, 2021)
In this article, theoretical data and graphic methodological recommendations on the teaching of the forty topics are given.